White prescriptions: the dangerous social potential for Ritalin and other psychotropic drugs to harm black boys - Fitzgerald, Terence D. (Paradigm Publ., 2009)
History and context -- The fueling of hate and control -- The yellow brick pathway to control -- Getting by with a little help from the feds -- Operation control: champaign, illinois -- Conclusion